The Ecological Veto in Islamic Law: Reconstructing Natural Resource Governance from Prophetic Precedents - Muhammad Zainuddin Zidan; Ali Mas’ud (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2026)
Extractive industrial practices increasingly exacerbate global socio-ecological degradation, revealing the structural limitations of conventional market-driven governance and economic cost-benefit models in internalizing environmental damage. While contemporary environmental literature offers technocratic frameworks, existing Islamic legal scholarship remains divided between abstract eco-theological norms that lack operational legal enforceability and secular administrative regimes that bypass religious jurisprudence. To address this gap, this study examines the historical-normative precedents of early Islamic natural resource statecraft as its primary object of analysis. Employing a qualitative historical-normative design, this research utilizes uṣūlī hermeneutical methods, specifically takhrīj al-manāṭ (extraction of legal ratio legis), and the analytical framework of maqāṣid al-sharī‘ah to evaluate canonical Hadith records regarding the revocation of Abyad bin Hammal’s salt mining concession and the institutionalization of the ḥimā Al-Naqī conservation zone. The findings demonstrate that early Islamic jurisprudence establishes an operational